Review Of Legal Disabilities In Regulation Of Immigration Intelligence Functions And Assessment Of Immigration Intelligence Functions Implementation - Azriel Fallah; Dimas Dwi Hartawan; Seyna Dina Olivia Manurung (LEGAL BRIEF, 2021)
Intelligence is something that has been done by every individual, from the smallest part to the biggest part of society. Intelligence means the act of collecting information for the purpose ending a case or preventing a problem to happen. Intelligence in Indonesia do their task and function in accordance with the Act number 17, 2011 about National Intelligence. As one of the Intelligence who works for the Ministry, Immigration Intelligence have to do their task in accordance with that Act. But, there is a problem that makes the implementation of Immigration Intelligence become a little hesitant, which is the differences between the Ministerial Regulation of Ministry of Law and Human Rights (Permenkumham) number 30, 2016 and the Act number 17,2011 in the function that is being held by Immigration Intelligence, in which Permenkumham didn' doesn't include the raising function. Dealing with that, there are a lot of polict that been made to cover that mistakes. Other than that, the advantages and disadvantages that makes the Immigration Intelligence can't do their task optimally that would be discussed, one of them is the lack of coordination and analysis with other units before holding an operation.